Penerapan ABSS Premier V.20 Pada Pengolahan Data Keuangan PT. Maxima Asta Wisesa Bekasi - Fajar Agustini; Melisa Triani (LPPM Universitas Bina Sarana Informatika, 2021)
Every company, which are service company, trading company or manufacturing company generally requires a system in carrying out the operational activities. Using accounting computer application for every companies in running their business can becomes more effective and efficient. PT. Maxima Asta Wisesa is a manufacturing company which are engaged in producing cosmetics and tolling services. The recording system and financial transaction data at PT. Maxima Asta Wisesa still has not implemented with a computerized system, so their reporting is to be hampered. The development of technology for recording financial transactions with the creation of ABSS Premier Version 20 software is very helpful for companies in processing financial transaction data. The results of the apllication shows that the ABSS Premier can run well and overcome the problems transaction data of sales, purchases, receive money, spend money and financial reports at PT. Maxima Asta Wisesa.